PENGEMBANGAN EKOWISATA BERKELANJUTAN DI WISATA GOA LAWAH, DESA LEBAH SEMPAGE, KECAMATAN NARMADA - Saufani, Rifqi; Rahim, Karina; Umur, Islahul; Aulia, Baiz Azmy Ridha; Mariani, Nining; Bilarakhma, R.R Novda Salsa; Ramdhani, Mohamad Yogi Pratama; Syazwani, Azlina; Zikro, Patania; Wiherlina, Bq Vidia Maulla (Jurnal Wicara, 2024)
This article deals with sustainable ecosystem development in Tourism Goa Lawah, Lebah Sempage Village, Narmada district, which has significant potential in improving the economic well-being of local communities. By exploiting the existing tourism potential, the management carried out by the tourism awareness group (POKDARWIS) and cooperation with the village government aims to create new jobs and increase public income through various economic activities, such as the rental of camping equipment and the sale of food. Despite challenges such as insufficient infrastructure and minimal environmental awareness, an inclusive and sustainable approach is expected to ensure that the economic benefits of the ecosystem are not only by external investors, but also by local communities. The study uses qualitative methods to analyze the impact of ecosystem development on local economies and provides recommendations for raising public awareness and participation in environmental conservation and tourism management. The results show that the development of ecosystems in Goa Lawah can contribute to reducing poverty and improving the quality of life of the Lebah sempage Village.